Peran Tasawuf dalam Kehidupan Materialis Masyarakat Modern - Bakis Fadlatunnisa (UIN Sunan Gunung Djati Bandung, 2022)
This study aims to discuss the role of Sufism in the materialist life of modern society. This study uses a qualitative approach by applying a descriptive-analytical method. The results and discussion in this study indicate that Sufism can be a solution to human anxiety and greed. This research concludes that Sufism can be a remedy for materialist attitudes which become a competition arena to show one's property or wealth, the more people pursue worldly pleasures the further away people like this are from their God. Therefore, there is a need for spiritual spiritual handling so that a person avoids feeling anxious, greedy, and upset because of material worries.